Influence of Profitability, Leverage and Company Growth on Dividend Policy (Study on Main Board and Development Board Index Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period) - Made Ari Dwipayani, Ni; Gde Wahyu Purna Anggara, I Wayan (Dinasti Publisher, 2025)
Dividend policy is a decision regarding the profit earned by the company which is distributed to shareholders as dividends or retained in the form of profit for future investment payments. This study aims to empirically analyze the effect of profitability, leverage, and company growth on dividend policy. The population of this research is the main board index companies and development boards listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample selection used purposive sampling technique so that a sample of 30 companies. The data analysis technique used in the study was multiple linear regression test. The results of this study indicate that profitability has a positive effect on dividend policy, leverage has a positive effect on dividend policy, and company growth has a negative effect on dividend policy.